Bowman layer transplantation in eyes with progressive advanced keratoconus - O. G. Oganesyan; V. R. Getadaryan; P. V. Makarov; A. A. Grdikanyan (Российский офтальмологический журнал, 2019)
Purpose: to study the efficiency of Bowman layer transplantation (BLT) in corneal stroma for the treatment of progressive keratoconus (KC).Material and methods. 30 patients (30 eyes) with progressive KC stages III to IV (according to Amsler — Krumeich classification), underwent BLT into a mid-stromal pocket. At the time of surgery, the patients were 14 to 37 (averagely 26.6 ± 6.2 years). Before and after the surgery, the maximum keratometry index (Kmax) and the corneal thinnest point (CTP) values were determined. Also, we evaluated visual acuity before and after surgery in scleral contact lenses, endothelial cells density (ECD) and the depth of graft location. The indication for surgery was the refusal of corneal transplantation, progression of KC, contraindications for ultraviolet crosslinking or implantation of intracorneal ring segments based on the CTP and Kmax values. The follow-up continued 6 to 36 months (averagely, 26.6 ± 6.0 months).Results. Throughout the observation period, no intra or postoperative complications associated with BLT or deterioration of CTP, Kmax or best corrected visual acuity (BCVA) in scleral lenses were noted.Conclusions. Kmax, CTP and ECD values remaining stable during the follow-up is the evidence of a stabilizing BLT effect on the KC progression. The absence of BCVA decrease in scleral lenses indicates a functional safety of BLT.